2010
DOI: 10.1073/pnas.1003063107
|View full text |Cite
|
Sign up to set email alerts
|

Osmotically induced synthesis of the dipeptide N-acetylglutaminylglutamine amide is mediated by a new pathway conserved among bacteria

Abstract: The dipeptide N-acetylglutaminylglutamine amide (NAGGN) was discovered in the bacterium Sinorhizobium meliloti grown at high osmolarity, and subsequently shown to be synthesized and accumulated by a few osmotically challenged bacteria. However, its biosynthetic pathway remained unknown. Recently, two genes, which putatively encode a glutamine amidotransferase and an acetyltransferase and are up-regulated by osmotic stress, were identified in Pseudomonas aeruginosa. In this work, a locus carrying the orthologou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 38 publications
2
49
0
1
Order By: Relevance
“…S3 in the supplemental material) (7). A B728a mutant that lacked the ggnAB genes required for NAGGN synthesis (27,34), designated B7⌬ggn, exhibited impaired osmotolerance but only at high NaCl concentrations (Ͼ0.6 M) ( Fig. 4A and B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S3 in the supplemental material) (7). A B728a mutant that lacked the ggnAB genes required for NAGGN synthesis (27,34), designated B7⌬ggn, exhibited impaired osmotolerance but only at high NaCl concentrations (Ͼ0.6 M) ( Fig. 4A and B).…”
Section: Resultsmentioning
confidence: 99%
“…4C; see Fig. S4A); the operon contained two putative genes downstream of ggnAB that are not required for NAGGN synthesis (34). A trehalose-deficient DC3000 mutant, designated DC⌬tre (Table 1), showed a much greater growth delay than DC⌬ggn in MinAS medium, with a mutant that lacked the loci for both NAGGN and trehalose production showing the most severe reduction in osmotolerance ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We assayed the trehalose content of P. stutzeri A1501 cells grown in MM63 containing either 50 mM (low osmolarity) or 700 mM (high osmolarity) NaCl and found increased amounts of trehalose in the high-osmolaritystressed cells (data not shown), in accord with the data reported by Seip et al (58) for the P. stutzeri DSM5190 type strain. Genes (asnO and ngg) encoding a glutamine amidotransferase (AsnO) and N-␥-acetylglutaminyl glutamine acetyltransferase (Ngg) for the synthesis of NAGGN (52) are also present in the genome sequence of P. stutzeri A1501, but we have not assessed the formation of this peptide in osmotically stressed cells.…”
Section: Resultsmentioning
confidence: 99%
“…The uptake of compatible solutes by microorganisms is typically preferred, possibly for energetic reasons (48), over their de novo synthesis. It is thus often observed that the uptake of compatible solutes suppresses the expression of biosynthetic genes for these compounds (53). To test whether this was also the case for the proHJ genes, we grew the ⌽(proHtreA)1 reporter gene fusion strain JSB7 in SMM with increasing concentrations of NaCl in either the absence or presence of glycine betaine (1 mM).…”
Section: Vol 193 2011 Adaptation Of B Subtilis To Osmotic Stress 5341mentioning
confidence: 99%